Alterations in the p53 gene and the clonal evolution of the blast crisis of chronic myelocytic leukemia. - Ahuja, H (1989)
Molecular mechanisms responsible for the clinical progression of chronic myelocytic leukemia to its accelerated phase or to blast crisis have not been defined. We found alterations of the p53 gene (p53 is a 53-kDa nuclear protein) including deletions and rearrangements in 8 of 34 patients in blast crisis and 1 of 4 patients in the accelerated phase, but in only 1 of 38 patients in the chronic phase of chronic myelocytic leukemia. Only two other examples of p53 gene alterations were found among 203 patients with hematologic malignancies and solid tumors. Transcripts of the p53 gene were uniformly found in chronic-phase cells, but gene expression was variable in blast crisis, and transcripts were reduced or undetectable in 10 of 16 patients. Heterogeneous alterations in the structure and expression of the p53 gene appear to be relatively frequent in blast crisis and may be involved in the evolution of disease.